If you say something, see something. - EIDahab, Mai Abu; Ben-Ner, Guy; Sperlinger, Mike; TENT., Rotterdam (Rotterdam : Piet Zwart Institute, 2010)
Amar, Ghislain ; Brunen, Derek ; Duta, Diana ; Fernandes, Priscila ; Kok, Tom ; Knox, Bitsy ; Slater, Marnie ; Ross, Bat Sheva ; Tan, Jay ; Taylor, Selina ; van Leeuwen, Sjoerd ; Wu, Annie
If you say something, see something., TENT., Rotterdam, 9.07 - 22.08.2010
kunstcatalogus